Prevalence and associated factors of occupational injuries among garment and textile workers: Evidence from the Bangladesh Labour Force Survey 2016–17 - Md. Tariqujjaman; Arifa Farzana Tanha; Md. Alamgir Hossain; Abul Hares; Md. Matiur Rahaman; Nadia Sultana; Fahmida Ferdous; Md. Mehedi Hasan; Md. Rashidul Azad (PLoS ONE, 2025)
Annually, numerous workers face job loss, injuries, and fatalities due to various occupational injuries (OIs). However, less is known regarding the burden of OIs and their associated factors in the textile and garment industries in Bangladesh. This study aimed to determine the prevalence of OI and the individual and job-related factors associated with OI among textile and garment workers in Bangladesh. We analyzed cross-sectional data of 13,738 workers collected during 2016–2017 from the nationally representative Bangladesh Labor Force Survey. We employed multiple Firth logistic regression models to explore the different levels of associated factors of OI. The overall prevalence of OI was 1.8%, with a higher prevalence in the textile industry (3.8%) compared to the garment industry (1.2%). Within the textile industry, jute manufacturing exhibited the highest prevalence (12.3%), while in the garment sector, the embroidery and wearing industries had the highest prevalence (1.8%). Adjusted models revealed that, in the textile industry, migrant workers had higher odds of OI (Adjusted Odds Ratio, AOR = 1.65; p = 0.017) compared to non-migrant workers. In the garment industry, male workers (AOR = 1.95; p = 0.002) and those working over 48 hours per week (AOR = 1.70; p = 0.063) were at greater risk of OI. A hazardous work environment significantly increased the odds of OI in both industries (textile: AOR = 13.06; p < 0.001; and garment: AOR = 3.13; p < 0.001). Additionally, garment workers without adequate protective equipment or cloth while working had a higher likelihood of OI (AOR = 1.90; p = 0.006). Regionally, workers in the Barisal division had higher odds of OI in the textile industry. Although the overall prevalence of OI was low, the disproportionate burden among certain subgroups, especially in jute manufacturing and the manufacture of spooling and thread, highlights critical areas for intervention. Improving workplace safety through the provision of protective equipment and a safer working environment is essential to mitigating OI in the textile and garment industries of Bangladesh.